The Relationship Of The Use Of Hormonal Contraceptives On Sexual Function In Family Planning Acceptors At Lubuk Buaya Health Center, Koto Tangah District Padang City - Dani Kartika Sari; Ferdinal Ferry; Ida Rahmah Burhan (Andalas Obstetrics And Gynecology Journal, 2024)
Background: Decreased sexual desire (libido) in recipients of Depo Medroxyprogesterone Acetate (DMPA) injectable contraceptives, although rare and not experienced by all women, can occur with long-term use due to hormonal changes, resulting in drying of the vagina, which causes pain during intercourse and ultimately decreased sexual desire or arousal. Objective: to determine the relationship between hormonal contraception and sexual function in hormonal birth controlacceptors at the Lubuk Buaya Community Health Center, Koto Tangah District, Padang City. Method: The research was observational with a cross-sectional approach on family planning acceptors at Lubuk BuayaCommunity Health Center, Koto Tangah District, Padang City, from November 2023 to January 2024. A total of 75respondents who were active hormonal family planning acceptors at Lubuk Buaya Community Health Center, Koto District Tangah Padang City, were sampled. Results: Bivariate analysis of the relationship between hormonal contraceptive use and sexual dysfunction using Chi-square resulted in a p-value>0.05. Conclusion: There is no significant relationship between the use of hormonal contraception and sexual dysfunction in hormonal birth control acceptors at the Lubuk Buaya Community Health Center, Koto Tangah District, Padang City.